2021
DOI: 10.1038/s41598-021-95576-5
|View full text |Cite
|
Sign up to set email alerts
|

Depression, combined visual and hearing impairment (dual sensory impairment): a hidden multi-morbidity among the elderly in Residential Care in India

Abstract: To report the prevalence of depression and its association with combined visual (VI) and hearing impairment (HI) in the elderly in residential care in India. Participants aged ≥ 60 years were recruited from 41 homes. Data on personal and sociodemographic information were obtained. Visual acuity was measured using the logMAR chart. Patient Health Questionnaire (PHQ-9) was used to assess depression, and the Hearing Handicap Inventory for the Elderly Screening (HHIE) was administered to assess hearing status. Dat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 62 publications
1
12
1
Order By: Relevance
“…In addition, our research model explains a 14.5% variance in health status, which is comparable with prior research focusing on health status, ranging from 9.0% to 13.8% (e.g., Hale et al, 2005;Dallinga et al, 2015;Suso-Ribera et al, 2019). Although health status is impacted by other factors like hearing impairment (Marmamula et al, 2021), negative emotions (Lepp, Barkley, & Karpinski, 2014), and poor eyesight (Marmamula et al, 2021), our findings reveal that mobile application usage is an important factor that impacts health status by drawing on users' physiological and psychological resources.…”
Section: Discussionsupporting
confidence: 84%
“…In addition, our research model explains a 14.5% variance in health status, which is comparable with prior research focusing on health status, ranging from 9.0% to 13.8% (e.g., Hale et al, 2005;Dallinga et al, 2015;Suso-Ribera et al, 2019). Although health status is impacted by other factors like hearing impairment (Marmamula et al, 2021), negative emotions (Lepp, Barkley, & Karpinski, 2014), and poor eyesight (Marmamula et al, 2021), our findings reveal that mobile application usage is an important factor that impacts health status by drawing on users' physiological and psychological resources.…”
Section: Discussionsupporting
confidence: 84%
“…This was compared to the percentages reported by a study of disabled Ethiopians before COVID-19 (38.3%), 24 visual impairment among patients with cataracts in Australia (31.2%), 25 older adults with visual impairment in England (29.6%), 26 older people with visual impairment in Spain (27.5%), 27 older persons with vision loss in Netherlands (26.5%) 28 and older adults with visual impairment living in residential care in India (20.9%). 29 The prevalence of depression in our study was lower than those reported during the COVID-19 pandemic for older patients with visual impairment in Bangladesh (58.1%) 30 and patients with visual impairment in Brazil (53.9%). 31 It is well recognized that depression is a key cause of disability globally and contributes to the global burden of disease.…”
Section: Discussioncontrasting
confidence: 71%
“…Hearing, vision, or mobility loss impede people's ability to communicate and socialize. Correlational evidence suggests that this may increase their sense of isolation and deteriorate mental health (Marmamula et al 2021), highlighting the importance of supporting the elderly in coping with these disabilities. The first step is diagnosis.…”
Section: Interventions To Improve Physical Health and Activitymentioning
confidence: 99%